IMPLEMENTATION OF PROBLEM-BASED APPROACH TO IMPROVE ELEMENTARY SCHOOL STUDENTS' LEARNING OUTCOMES - Agus, Jufri; Yusnan, Muhammad; Farisatma; Acoci (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2024)
Problem-Based Learning (PBL) is a learning method that emphasizes solving real problems to improve student understanding. The aim is to determine the Application of Problem-Based Approach to Improve Social Studies Learning Outcomes in Grade IV Students of SD Negeri 2 Wameo. The type of research used in this study is Classroom Action Research (CAR), which aims to improve social studies learning outcomes through the application of the Problem-Based Approach. CAR is carried out systematically in a classroom environment with the aim of improving the quality of learning and student learning outcomes. Based on the recapitulation results from the pre-cycle to cycle II, there was a significant increase in student learning completion after the application of the problem-based approach. In the pre-cycle, the majority of students had not achieved completion, but through improvements in learning strategies in cycles I and II, the number of students who completed continued to increase, while students who did not complete decreased. This success shows that more active and innovative learning methods can effectively improve student understanding. Thus, the problem-based approach can be used as a sustainable strategy to improve the quality of social studies learning.